The mossy forest ecosystem as field laboratory for learning basic ecological concepts - Lorenzo, Betina Bernardino ([Quezon City s.n.], 1973)
The mossy forest ecosystem of Mt. Santo Tomas was investigated such that it enumerates, analyzes, and integrates its basic components (abiotic and biotic factors, the last being composed in turn into producers, consumers and decomposers). In addition, this study presents an outdoor laboratory design which includes activities for students in the investigation of ecological concepts.
Thesis (M.A.T.)--University of the Philippines.
Keywords: Forests ecology -- Study and teaching; Forestry schools and education